LB002 Long term effect of field triage on times to endovascular treatment for emergent large vessel occlusion. (26th July 2022) - Jayaraman, M; Baird, G; Ouediat, K; Paolucci, G; Haas, R; Torabi, R; Moldovan, K; Rhodes, J; Potvin, J; Alexander-Scott, N; Yaghi, S; Madsen, T; et al.
Abstract : Background: Delays to endovascular therapy (EVT) for stroke may be mitigated with direct field triage to EVT centers. Objective: To compare times to treatment over a five-and-a-half-year span between two adjacent states, one with field triage one without, served by a single comprehensive stroke center (CSC). Methods: A single CSC serves our region of nearly 1.5 million persons, across two adjacent states. During the study period, one of the two states implemented severity-based triage for suspected ELVO, while in the other state, patients were transported to the closest hospital regardless of severity. We compared times to treatment with EVT and alteplase, and clinical outcomes between these two states. To account for potential imbalances between the groups, we also performed a matched pairs analysis, matching on date treated, NIHSS and time from field to CSC. Results: 639 patients met criteria, 407 in State 1 (with field triage) and 232 in State 2 (without field triage). After implementing severity-based triage, for every year, the odds of patients taken directly to the CSC in State 1 increased by 75.1% (OR: 1.75, 95% [1.47, 2.09], p<.0001); by five years, over 90% of the EVT patients in State 1 were brought directly to the CSC. In State 1, Scene to EVT decreased 6% (or 8.13 minutes, p=.0004) every year but no decrease was observed for State 2 (<1%, p=.94), see figure 1 . These rates of reduction were significantly different (p=.0027). Cumulatively over 5.5 years, there was a reduction of 43 minutes in time to EVT in State 1, but no change in State 2. While time to EVT decreased, there was no increase in time to intravenous thrombolysis. For the matched pairs, in State 1 there was a reduction every year in time to EVT of 8% (or 10.04 minutes, 95% CI[3.60, 16.49]), p=.0014) but no decrease in State 2 (<1% or .997, 95% CI [.97, 1.03], p=.89); these rates of reduction were significantly different (p=.003). Clinical outcomes at 90 days were significantly better in State 1, both for the entire cohort (all OR: 1.22, 95% CI[1.07, 1.40] p=.0032 and for those independent at baseline 1.36, 95% CI[1.15, 1.59], p=.0003), as well as for the matched pairs (all patients OR: 1.22, 95% CI[1.01, 1.48] p=.0439 and independent at baseline 1.37, 95% CI[1.06, 1.76], p=.0153). Conclusions: Comparing adjacent states over time, the implementation of severity-based field triage significantly reduced time to EVT and improved clinical outcomes. Disclosures: M. Jayaraman: None. G. Baird: None. K. Ouediat: None. G. Paolucci: None. R. Haas: None. R. Torabi: None. K. Moldovan: None. J. Rhodes: None. J. Potvin: None. N. Alexander-Scott: None. S. Yaghi: None. T. Madsen: None. K. Furie: None. R. McTaggart: None.